The role of cyclic vitamin therapy as a non-hormonal method of rehabilitation treatment of menstrual disorders after an inflammatory disease of the pelvic organs - A F Mikhelson (IP Berlin A.V., 2016)
Intensity of generative functions violations depends on the frequency of the transferred inflammatory diseases of the pelvic organs (pelvic inflammatory disease), their etiology, treatment tactics and approaches to rehabilitation. With the increase in the number ofepisodes of the disease increasing, the frequency of tubal infertility and ectopic pregnancy also rises. The most characteristic effects of deferred PID are different forms of menstrual disorders. The inclusion in the program of treatment and prevention of disorders of vitamins and minerals of the menstrual cycle is a promising direction of finding an effective and safe approach to therapy. The results of a prospective study of the effectiveness of the two-phase vitamin-mineral complex Ciklovita® used by patients of reproductive age with oligomenorrhea, which developed after previous PID indicate the feasibility of its application.